Rancang Bangun Aplikasi Sistem Pakar Penentu Kesehatan Makanan Khas DKI Jakarta Berbasis Android dengan Metode Backward Chaining - Afriyani Agustin; Perani Rosyani (CV. Shofanah Media Berkah, 2023)
In daily life, food plays a crucial role in maintaining one's health and well-being. Regional cuisine also holds cultural value and serves as an attraction for both local and international tourists. DKI Jakarta, as the capital city of Indonesia, offers a variety of local dishes that showcase the culinary diversity of Indonesia. However, when it comes to selecting healthy and nutritionally suitable food according to individual needs, people often face challenges in obtaining information about the nutrition and health value of specific foods. Additionally, there may be specific considerations to take into account, such as health conditions or dietary preferences. In this context, the development of an expert system application can be an effective solution to assist users in determining the suitability and health value of DKI Jakarta's local food. An expert system is a computer system that utilizes knowledge acquired from domain experts to provide relevant recommendations or solutions to users. The Backward Chaining method used in this application development allows users to input their symptoms or dietary preferences, and the system analyzes this information based on programmed knowledge rules. Leveraging Android technology, this application provides easy and convenient access to users through their mobile devices. Through the design and development of this Android-based expert system application for determining the healthiness of DKI Jakarta's local food using the Backward Chaining method, it is expected that users can easily evaluate the food they consume based on their needs and dietary preferences. This application also aims to raise awareness about the importance of choosing healthy and nutritious food in everyday life, while promoting DKI Jakarta's local cuisine as part of Indonesia's cultural richness. Therefore, the objective of this research is to design and build an Android-based software information system for determining the healthiness of DKI Jakarta's local food using the Backward Chaining method.